2023
DOI: 10.1146/annurev-vision-111022-123758
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptual Science of Augmented Reality

Abstract: Augmented reality (AR) systems aim to alter our view of the world and enable us to see things that are not actually there. The resulting discrepancy between perception and reality can create compelling entertainment and can support innovative approaches to education, guidance, and assistive tools. However, building an AR system that effectively integrates with our natural visual experience is hard. AR systems often suffer from visual limitations and artifacts, and addressing these flaws requires basic knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…The quality of blending virtual and physical content is confined by a constellation of factors, including (1) hardware constraints such as latency, optical distortions, and tracking inaccuracies that can result in the misplacement of virtual objects within the real environment, and (2) disparities in the appearance of virtual and physical components, encompassing differences in color and illumination. There is a great body of knowledge addressing these perceptual incongruencies and how different technologies cope with these [2,4,9,10,27]. Different AR display technologies inhere different incongruencies.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of blending virtual and physical content is confined by a constellation of factors, including (1) hardware constraints such as latency, optical distortions, and tracking inaccuracies that can result in the misplacement of virtual objects within the real environment, and (2) disparities in the appearance of virtual and physical components, encompassing differences in color and illumination. There is a great body of knowledge addressing these perceptual incongruencies and how different technologies cope with these [2,4,9,10,27]. Different AR display technologies inhere different incongruencies.…”
Section: Introductionmentioning
confidence: 99%
“…3 For a recent review, see Ref. 4 There is a lack of data quantifying the perceptual impact of varying magnitudes and directionality of AR VAC. This lack of data is a major limitation when designing appropriate hardware and/or software solutions to mitigate the effects of AR VAC.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that VAC impaired interaction with a virtual hand suggesting that VAC impairs eye‐hand coordination 3 . For a recent review, see Ref 4 …”
Section: Introductionmentioning
confidence: 99%